How to improve the socially responsible behavior? Experiences in a clinical analysis enterprise in the South East of Mexico - Barroso Tanoira, Francisco Gerardo (2021)
The general diagnosis for evaluating the socially responsible behavior of a clinical analysis laboratory is presented, as well as the intervention for improving such behavior, as part of the requirements of the acceleration program of the Transfer Office of a higher education institution in the South East of Mexico. The intervention, through two participative action-research cycles, was performed from July to November in 2018, with a post test at the end of the last one. Results show a significant improvement in the environment preservation results, considering the socially responsible behavior as satisfactory in general. And although the differences were not significant in the other ambits, it is important to highlight leadership for motivating and involving employees in action research processes.